The Development of an Algorithm to Identify Potential Social Security Disability Beneficiaries. (December 2013) - Frey, William; Riley, Jarnee; Gonin, Rene; Kalton, Graham; Weathers, Robert R.; Kalasunas, Susan A.; Stegman, Michelle L.
The Social Security Administration funded the development of a screener that could accurately classify household members into one of four disability groups (likely disabled, possibly disabled, not disabled, or current social security disability beneficiaries) for purposes of a larger national study. The authors developed a questionnaire, tested five screener algorithms on data from a pilot study, and assessed the performance of each screener in identifying individuals who are likely disabled, possibly disabled, and not disabled. An algorithm using the item response theory methodology of Rasch modeling offered the greatest improvement over the original screener algorithm and appeared to be quite superior to the other alternatives.